THE ROLE OF THE FAMILY IN THE SOCIALIZATION OF THE INDIVIDUAL, CONTEMPORARY PROBLEMS AND PERSPECTIVES - Nargiza Karkashadze; Tengiz Kuprashvili; Tinatin Gugeshashvili (International Journal of Innovative Technologies in Social Science, 2023)
In today’s world, great attention is paid to the protection of children’s rights and the process of their socialization. This is mainly due to the increasing statistics of forced labor, involvement in crime, rape, bullying, abandonment, beating, etc towards children, both in the family and at school. In order to study the process of socialization of a person (a child) in the family, we addressed two methods of research: field research through a questionnaire and expert research, the analysis of which revealed very interesting facts and opinions. The article also lists the measures that were implemented to address the problems associated with effectively managing the process of socialization of an individual in the family In addition, there are opinions of experts on the process of socialization of the child in the family given, as well as the recommendations of the authors, the implementation of which will help to raise public awareness about the processes of socialization of the individual in the family, which will reduce the fact of violation of children’s rights and make this process effective. The article also provides a list of measures that will help in effectively managing the process of socialization of the individual in the family, namely: • The master’s program "Education Science" (in Georgian and English languages) will integrate the course - Child Rights and Advocacy; • The subject “Child rights and advocacy” will also be included in the 60-credit integrated master and bachelor teacher training program; • The subject ”Child rights” was integrated in the bachelor’s program "Preschool Education".